Pengaruh Pemahaman Akuntansi, Citra Profesi, Dan Pertimbangan Finansial Terhadap Minat Mahasiswa Akuntansi Menjadi Seorang Auditor: (Studi Pada Mahasiswa Jurusan Akuntansi Universitas Hindu Indonesia) - Ni Wayan Sepiani; Sang Ayu Putu Arie Indraswarawati; Putu Cita Ayu (UNHI Press, 2026)
Auditor is considered the career most accounting students can choose because more and more companies in Indonesia have gone public and have more than one shareholder. In an effort to keep the business running without any irregularities in financial reports, the Company needs to monitor and require valid information about the activities carried out by management in the Company. The population in this study was 338 accounting study program students with a sample size of 184 students. The analysis technique used is multiple linear regression. The research results show that understanding accounting, professional image, and financial considerations have a positive and significant effect on students' interest in becoming an auditor.